2019
DOI: 10.1093/nar/gkz528
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 promotes transcription of a subset of NRF2 targets by mono-ADP-ribosylating BAF170

Abstract: SIRT6 is critical for activating transcription of Nuclear factor (erythroid-derived 2)-like 2 (NRF2) responsive genes during oxidative stress. However, while the mechanism of SIRT6-mediated silencing is well understood, the mechanism of SIRT6-mediated transcriptional activation is unknown. Here, we employed SIRT6 separation of function mutants to reveal that SIRT6 mono-ADP-ribosylation activity is required for transcriptional activation. We demonstrate that SIRT6 mono-ADP-ribosylation of BAF170, a subunit of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 60 publications
0
46
0
Order By: Relevance
“…HDACs participate in the crosstalk between RNAP2 C-terminal domain acetylation and phosphorylation (Wang et al, 2009;Blank et al, 2017;Ali et al, 2019). SIRT6 recruits and mono-ADP-ribosylates switch/sucrose non-fermenting (SWI/SNF) related, matrix associated, actin dependent regulator of chromatin subfamily c member 2 (SMARCC2/BAF170) to form active chromatin at the enhancer of heme oxygenase-1, which subsequently recruits RNAP2 (Rezazadeh et al, 2019). SIRT6 can also bind p53 to effectively recruit RNAP2 to local promoters (Li et al, 2018).…”
Section: Transcriptional Activationmentioning
confidence: 99%
“…HDACs participate in the crosstalk between RNAP2 C-terminal domain acetylation and phosphorylation (Wang et al, 2009;Blank et al, 2017;Ali et al, 2019). SIRT6 recruits and mono-ADP-ribosylates switch/sucrose non-fermenting (SWI/SNF) related, matrix associated, actin dependent regulator of chromatin subfamily c member 2 (SMARCC2/BAF170) to form active chromatin at the enhancer of heme oxygenase-1, which subsequently recruits RNAP2 (Rezazadeh et al, 2019). SIRT6 can also bind p53 to effectively recruit RNAP2 to local promoters (Li et al, 2018).…”
Section: Transcriptional Activationmentioning
confidence: 99%
“…[81,82] Recently, Rezazadeh et al reported that SIRT6 also ADP-ribosylates BAF170 (SMRC2), a component of the SWI/SNF chromatin remodeling complex, in order to promote the expression of NRF-2 responsive genes in response to oxidative stress. [83] This role of SIRT6 is particularly interesting because it "activates" (as opposed to represses) gene expression. This may be another case where SIRT6 activity depends on other factors or context in vivo that confers specificity.…”
Section: Genome and Epigenome Stabilitymentioning
confidence: 99%
“…Chromatin immunoprecipitation assay was performed as described earlier (Rezazadeh et al, 2019). The immune complexes were captured using protein A −Sepharose beads.…”
Section: Chromatin Immunoprecipitation Assay (Chip)mentioning
confidence: 99%